Profile of the newborn admitted to the Neonatal Intensive Care Unit: an integrative review (Research, Society and Development, 2022)
The study must know the publications on the profile of the newborn hospitalized in the Neonatal Intensive Care Unit in the last 10 years. An integrative review was carried out, based on searches in the Online System of Search and Analysis of Medical Literature, Latin American and Caribbean Literature on Health Sciences and Nursing Database, using the keywords: newborns; neonatal intensive care units connected by the boolean AND. Select published and Spanish studies from 2011 to 2021, in English, Portuguese. Resulting in 31 articles. It resulted in three categories to present the results: aspects of the birth of neonates admitted to the Neonatal Intensive Care Unit and risk factors for children; main clinical diagnoses and length of stay of neonates in the Neonatal Intensive Care Unit; and maternal and sociodemographic data of the neonate admitted to the Neonatal Intensive Care Unit. From the review, it was possible to know the profile of neonates admitted to the Neonatal Intensive Care Unit, in several aspects, with the prevalent profile of male newborns, born by cesarean section, with low birth weight and diagnoses of prematurity and /or respiratory syndromes.